The legality of medical cannabis from the Islamic perspective - Shahrul Mizan Ismail,; Ekmil Krisnawati Erlen Joni,; Rohaida Nordin, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Medicinal cannabis has been used for over 6000 years, and clinical trials have revealed its many therapeutic benefits. Despite its medicinal values and therapeutic benefits, Muslim countries are reluctant to accept the legal use of medicinal cannabis. Currently, Malaysian law prohibits the use of cannabis, either recreationally or medically. As a result, those who use cannabis for medical purposes may face severe punishment. Due to desperate situations, some Muslims purchase cannabis illegally through the black market for self-medication without knowing the legal status of access to cannabis in Islam. Therefore, this article intends to investigate the legal position of cannabis and the extent of cannabis prohibition in Islam. In achieving the objectives, this paper will review the debates between schools of Islamic thought and examine the approach of Muslim jurists in recognising the therapeutic benefits of cannabis through content analysis. Findings show that it is permissible to consume cannabis for medical purposes in Islam under certain situations, and the act of purchasing cannabis from the black market goes against Islamic principles. It is hoped that this article will provide enlightenment on these issues, especially to Muslims around the world, to correct any misapprehension. It is suggested that Muslim countries participate in conducting more research on the medicinal benefits of cannabis. Finally, to address the issues of misgivings among patients requiring legal medicinal cannabis, it is hoped this study will help to equip Muslim doctors with the requisite knowledge on the position of medical cannabis.